2012
DOI: 10.20533/licej.2040.2589.2012.0118
|View full text |Cite
|
Sign up to set email alerts
|

A Fairness Issue: Test Method Facet and the Validity of Grammar Sub-tests of High-Stakes Admissions

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Besides the previous studies, this study shares the importance of using more than one test formats with Khoii (2012. It supported the idea that the test method facet could be a strong source of bias in language testing. But this study added also that using one device for testing could affect our testing process and deprive the students from his chance to get better mark or better practice.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Besides the previous studies, this study shares the importance of using more than one test formats with Khoii (2012. It supported the idea that the test method facet could be a strong source of bias in language testing. But this study added also that using one device for testing could affect our testing process and deprive the students from his chance to get better mark or better practice.…”
Section: Discussionsupporting
confidence: 77%
“…In another words, the findings proved that the cloze procedure did not improve the subjects' knowledge of grammar any more than the multiple-choice Fatta 11 grammar test did. Khoii and Shamsi (2012) investigated the effects of different test formats on the measurement of grammatical knowledge by comparing the construct validities of two different formats of error-identification grammar tests (one with four options for each item and one with a no error option as the fifth option) and a multiple choice grammar test. After administering all the three tests to 131 Iranian EFL learners, it was found that while the TOEFL error-identification test enjoyed the highest level of construct validity, the no-error option in the SAT erroridentification test reduced its construct validity to a considerable degree, indicating that including no error options in admissions test does not allow an accurate evaluation of examinees' grammatical knowledge.…”
Section: Related Studies To Testing Grammarmentioning
confidence: 99%
“…Loh and Shih (2016) implemented an evidence-based approach toward test fairness. Moreover, the other studies mentioned previously, e.g., Khoii and Shamsi (2012) and Pishghadam and Tabataba'ian (2011), tried to explore the effect of other factors such as test format on test fairness; however, the present study considered the examination of the notion of fairness using TFF.…”
Section: Social Consequencesmentioning
confidence: 97%
“…In the same way, Khoii and Shamsi (2012) investigated the effects of different test formats on the measurement of grammatical knowledge by comparing the construct validities of two different formats of error-identification grammar tests and a multiplechoice grammar test. They compared these formats in MA entrance exam with TOEFL error identification test and SAT test.…”
Section: Literature Reviewmentioning
confidence: 99%